Validitas Lembar Kerja Peserta Didik (LKPD) Berbasis Problem Based Learning (PBL) pada Materi Inovasi Bioteknologi Fase F SMA/MA - Putri, Laisan; Sari, Liza Yulia; Rosba, Evrialiani (Biocaster : Jurnal Kajian Biologi, 2025)
In the learning process, students have used various teaching materials, such as modules, printed books, and Student Worksheets (LKPD). In addition, the learning process is also supported by the application of the problem-based learning model. One of the materials studied in grade XII of high school is biotechnology innovation. In the material, teachers use a problem-based learning model. This research aims to produce a LKPD based on problem based learning on valid biotechnology innovation materials in phase F of high school/MA. This type of research is a development research using a 4D model which includes four stages, namely define, design, develop, and disseminate. However, in this study, the disseminate stage was not carried out. The research instrument is in the form of a validation sheet used to test the validity carried out by three validators. The results of the study showed that the validity test by biology lecturers and teachers obtained an average score of 84.84% which is included in the very valid category. Thus, it can be concluded that the LKPD based on problem-based learning on the biotechnology innovation material phase F SMA/MA developed, is feasible to use.